Estimation of wheel wear in electrolytic in-process dressing (ELID) and grinding. (1st January 2011) - Biswas, I.; Senthil Kumar, A.; Rahman, M.
In this paper, wheel wear during ELID grinding is theoretically and experimentally investigated. Firstly, ELID grinding experiments are conducted to find the variation of wheel wear with different machining and dressing conditions. The results show that there are two states of the process; an initial state when the oxide layer on the wheel gradually wears off; a steady state marked by breakage of the oxide layer in discrete steps followed by restoration due to electrolytic dressing. The oxide formation method is modelled as a function of electrolytic current and oxide erosion is also modelled as a function of machining parameters. Wheel wear rate for the steady state of grinding, simulated from this model is in reasonable agreement with several other experimental values. During grinding, the actual depth of cut changes from the given value due to wheel wear. A new set of experiments are conducted where this actual depth-of-cut is measured from the work piece. The estimated wheel wear is then used to calculate the theoretical value of the actual depth-of-cut. This theoretical value is in good agreement with the experimentally obtained actual depth-of-cut. This is useful in attaining high profile accuracy of components.